Detection of Ralstonia solanacearum race 3 causing bacterial wilt of solanaceous vegetables in Kerala, using random amplified polymorphic DNA (RAPD) analysis - James, Deepa; Girija, D.; Mathew, Sally K.; Nazeem, P.A.; Babu, T.D.; Varma, A. Sukumara (Journal of Tropical Agriculture, 2006)
Nine strains of Ralstonia solanacearum (Smith) Yabuuchi et al. isolated from bacterial wilt affected plants of brinjal, chilli and tomato in three different agroclimatic zones of Kerala were compared based on the utilization of carbohydrates, hypersensitivity reaction on capsicum leaves and RAPD analysis. Among these, six isolates were grouped into Biovar III and three, into Biovar IIIA. The isolates belonged to Races 1 and 3. RAPD analysis with 10 decamer primers revealed a high degree of polymorphism among the isolates. The primer OPF 8 yielded a unique band of 1.45 kb size for Race 3. This could be considered as a marker for rapid identification of Race 3 isolates of R. solanacearum.